Band-gap and interface engineering by Ni doping and CoPi deposition of BiVO4 photoanode to boost photoelectrochemical water splitting. (1st January 2023) - Fang, Wanqing; Lin, Yimin; Xv, Rongzi; Shang, Xiaoying; Fu, Li
Abstract: Photoelectrochemical (PEC) water splitting can efficiently convert solar power into hydrogen energy. Herein, Ni-doped and CoPi-deposited BiVO4 photoanode (Ni:BiVO4 /CoPi) is synthesized by electrodeposition-solution drop casting process. The physicochemical characterizations show that Ni partially substitutes the V site, with the remainder being distributed on the sample surface in the form of NiOOH nanoparticles. CoPi is distributed on the BiVO4 surface in the form of amorphous particles. The photocurrent density of Ni:BiVO4 /CoPi is 3.2 times more than what is measured of the bare BiVO4 (5.90 mA/cm 2 at 1.23 VRHE ). Mott-Schottky tests show that Ni doping not only modulates the positions of conduction and valence band for the BiVO4, but that it also increases the carrier density. In comparison with bare BiVO4 (2.54 eV), UV-vis spectra analysis shows that the Ni:BiVO4 /CoPi band gap is reduced to 2.43 eV. The narrowed band gap extends light absorption and further facilitates the transport by bulk carriers of the Ni:BiVO4 /CoPi. Electrochemical impedance spectroscopy (EIS) results show that the surface charge transfer resistance of the Ni:BiVO4 /CoPi (91.49 Ω) is about half the amount of the BiVO4 . CoPi, a very effective oxygen evolution co-catalyst, is capable of optimizing the BiVO4 interfacial properties and accelerating injection by surface carriers. This work aims to design a novel Ni:BiVO4 /CoPi photoanode through band-gap and interface engineering to boost light absorption, carriers' transport and water oxidation kinetics for PEC water splitting.